Development of character and life skills through Islamic methods of teaching acquired science subjects at Islamic International Schools in Malaysia - Eissa, Manar; Khalid, Madihah (IIUM Press, 2018)
Islamic schools strive to achieve educational excellence while integrating religious and Islamic values into their curriculum. Yet, what makes an Islamic school really “Islamic” is not just its curriculum content, school personnel and religious values, but also the teaching methods employed by the teachers. For an integrated curriculum, what determines the success of its implementation is the teaching methods-how the shari’ah and the acquired sciences are taught to students. The aim of this paper is to investigate teachers’ perspectives of the potential benefits of using Quranic and Prophetic Teaching Methods (QPTMs) in acquired science classes to develop students' character and life skills. This study, which employed semi-structured one-on-one interviews, was conducted with six teachers who were teaching acquired science subjects at six International Islamic schools located in Selangor and Kuala Lumpur, Malaysia. The interviews were transcribed and the collected data were analyzed thematically. The findings revealed the teachers believe that QPTMs contribute significantly to the development of positive characteristics in students, such as respecting others, tolerance, open-mindedness, accepting of differences, patience, cooperation, and respect for the leader. At the same time, life skills such as communication, teamwork and leadership, as well as students’ self-confidence, self-appreciation, creativity, and spiritual aspects were also mentioned by the teachers as having improved. The research reveals the importance of QPTMs in teaching acquired science classes, and accentuates the importance of Muslim nations and schools to propagate their use in the classroom.